PENILAIAN EKONOMI SAMPAH KERTAS DI KOTA MEDAN - Ori Yani Yunilda; yunus afifuddin; Ridwanti Batubara (Program studi Kehutanan USU, 2012)
Problems were caused by used paper in each area are common problems, especially in urban area, for example Medan city. Types rubbish were generated from household level to the level of industries different, namely organic and inorganic. Example of organic rubbish is a used paper. One of the countermeasures for used paper are not to accumulate by collecting and selling used paper for recycling. The purpose of this study was to identify source used paper, the economic value and the benefits and the flow of marketing of used paper were collected and sold by people in the city of Medan. Based interviews with respondents, the source used paper were from household, market, office, shop and newspaper distributor. The greatest economic value is major collector that Rp. 115.162.500,- of year per respondent. The lowest economic value is collector that Rp. 1.055.000,- of year per respondents. Collected and sold of used paper while were contributing to the collectors that 27,85 % to total income respondents of month; the minor collectors that 38,87 % to total income respondents of month and the major collectors that 68,96 % to total income respondents of month. The flow are marketing of used paper from collectors, minor collectors, major collectors and end at the used paper mill. Key words: used paper, Medan, contribution, economic value